Genetics, Epigenetics, Cellular Immunology, and Gut Microbiota: Emerging Links With Graves’ Disease - Zhou, Fangyu; Wang, Xin; Wang, Lingjun; Sun, Xin; Tan, Guiqin; Wei, Wenwen; Zheng, Guangbing; Ma, Xiaomin; Tian, Dan; Yu, Hongsong (Frontiers in Cell and Developmental Biology, 2022)
Graves’ disease (GD) is a well-known organ-specific autoimmune disease characterized by hyperthyroidism, goiter, and exophthalmos. The incidence of GD is approximately 2.0–3.0% in China and 0.5–2.0% in Western countries. Due to the complex pathogenesis and etiology of GD, current treatment methods have great side effects that seriously endanger human health. Therefore, it is particularly important to understand the pathogenesis of GD. Various studies have shown that genetics, epigenetics, cellular immunology, and gut microbiota are all involved in the development of GD. Genetically, CD25 gene and VDR gene polymorphisms are involved in the development of GD by increasing the ratio of Th17/Treg cells. Epigenetically, miR-23a-3p and lncRNA-MEG3 lead to Th17/Treg imbalance and participate in the progression of GD. Moreover, commensal microbe deletion can disrupt Th17/Treg balance and participate in the occurrence of GD. The imbalance of Th17/Treg cells induced by genetics, epigenetics, and the gut microbiota plays a vital role in the pathogenesis of GD. Therefore, this article reviews the role of the genetics, epigenetics, cellular immunology, and gut microbiota in the pathogenic mechanism of GD. This may lead to proposing potential therapeutic strategies for future clinical application and providing promising therapeutic targets.